2009
DOI: 10.1063/1.3067463
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the demagnetizing field on the determination of the magnetocaloric effect from magnetization curves

Abstract: Articles you may be interested inEffect of hydrostatic pressure on magnetic entropy change and critical behavior of the perovskite manganite La0.4Bi0.3Sr0.3MnO3 J. Appl. Phys. 113, 023904 (2013) Field dependence of the magnetocaloric effect in materials with a second order phase transition: A master curve for the magnetic entropy change

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 7 publications
0
35
0
Order By: Relevance
“…12͒ or the influence of the demagnetization factor. 33 In the present work, we have used two references instead of one in order to assure that if a breakdown of the universal behavior of ⌬S M should occur, it could not be ascribed to any of the previously mentioned artifactual causes.…”
Section: ͮ ͑2͒mentioning
confidence: 99%
“…12͒ or the influence of the demagnetization factor. 33 In the present work, we have used two references instead of one in order to assure that if a breakdown of the universal behavior of ⌬S M should occur, it could not be ascribed to any of the previously mentioned artifactual causes.…”
Section: ͮ ͑2͒mentioning
confidence: 99%
“…We report upon the excellent magnetocaloric properties of Gd 53 Al 24 Co 20 Zr 3 amorphous microwires. In addition to obtaining the large magnetic entropy change (ÀDS M $ 10.3 J/kg K at T C $ 95 K), an extremely large value of refrigerant capacity (RC $ 733.4 J/kg) has been achieved for a field change of 5 T in an array of forty microwires arranged in parallel.…”
mentioning
confidence: 99%
“…Although the universal curve can be built with only one reference temperature, 12 it has been shown that the effect of the demagnetization factor 18 or the presence of a minority magnetic phase 19 can lead to a breakdown of the ⌬S M curve collapse. Two reference temperatures are used in the data treatment in order to avoid the effect of these extrinsic factors.…”
Section: A New Criterion To Distinguish the Order Of Magnetic Transitmentioning
confidence: 99%